FAMILY ROLES AND BLOOD GLUCOSE MANAGEMENT IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AT BANDAR LAMPUNG, INDONESIA - Eka Yudha Chrisanto; Yoko Saputra; Bahjatun Nadrati (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Diabetes Mellitus ranks 8th out of 10 major diseases in Lampung province with a prevalence of 0.4%. Based on Rikesdas Lampung Province results in 2013 it is known that DM pavelence reaches 0.7% with pravelensi in Bandar Lampung reaches 0.8% and for Public Health Services (Puskesmas) Panjang in 2017 cases of DM was found as much as 2145.Purpose: Knowing that the relation family roles and blood glucose management in patients with type 2 Diabetes Mellitus at Bandar Lampung, IndonesiaMethods: This was quantitative research type with analytical survey design and cross sectional approach. Population in this research were all patient of Diabetes Mellitus (DM) Type 2 in April 2018, at Puskesmas Panjang Bandar Lampung and the samples were 79 respondents given of questioner. The statistical test used is Chi Square test.Results: The frequency distribution of respondents aged between 60-69 years 54 (68.4%) respondents, female of 54 (68.4%) respondents, primary elementary education (45.6%) respondents, Duration of DM ≥ 5 years of 42 (53.2%) respondents, uncontrol blood sugar as many as 53 respondents (67.1%), poor family roles as many as 42 (53.2%) respondents, with p-value 0,000.Conclusion: There the relation of family roles and blood glucose management in patients with type 2 Diabetes Mellitus at Bandar Lampung, IndonesiaSuggestions: The management of Public Health Centre (Puskesmas) to give counseling to the family about the importance of family roles and blood glucose management in patients with type 2 Diabetes Mellitus